STRATEGI PEMBELAJARAN KOLABORATIF TIPE PREDICT DISCUSS EXPLAIN OBSERVE DISCUSS EXPLAIN (PDEODE) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI STOIKIOMETRI DI SMA NEGERI 9 PEKANBARU - Erna, Maria; Haryati, Sri; Hestivik, Chelsi (Jurnal Inovasi Pendidikan Kimia, 2019)
This study aims to determine the reduce of student misconception by applying collaborative learning strategy type of Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE) in discourse solubility equilibrium in class XI SMA Negeri 1 Pekanbaru. Instrument that used is three tier multiple choice test by using Certainty of Response Index (CRI). The study was an experiment with randomized control group pretest-posttest. The sample in this research is class XI MIA 9 as experiment class and class X1 MIA 7 as control class which is determined randomly after normality test and a homogeneity test. The experimental class is treated with the application of collaborative learning strategy type of Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE), while the control class without the application of collaborative learning strategy type of Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE). Data analysis for hypothesis testing is done using right-t test. Based on the results of data analysis obtained tct = 3,13 and ttable = 1,67 with ÃŽÂ± = 0,05, dk = 56. tcount > ttable is 3,13 > 1,67 means the application of collaborative learning strategy type of Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE) can improve student achievement on hydrocarbon subject in class XI SMA Negeri 1 Pekanbaru. The percentage reduction of misconception in the experimental class is 52,42%.